1995
DOI: 10.1001/jama.1995.03520330059038
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori, Gastroduodenal Disease, and Recurrent Abdominal Pain in Children

Abstract: There is strong evidence for an association between H pylori infection and antral gastritis and duodenal ulcer disease in children; however, data from randomized, double-blind, placebo-controlled treatment trials are required. There is weak evidence for an association with gastric ulcer and weak or no evidence for an association with recurrent abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
3
10

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(134 citation statements)
references
References 67 publications
5
116
3
10
Order By: Relevance
“…A strong association between H. pylori infection and PUD has been reported in many studies (13,14). In a meta-analysis, the prevalence of H. pylori infection in children with duodenal ulcer was reported as 92% (range: 30-100) (16). In our study, more than half of the children were infected with H. pylori in both the gastric ulcer and duodenal ulcer group.…”
Section: Discussionsupporting
confidence: 63%
“…A strong association between H. pylori infection and PUD has been reported in many studies (13,14). In a meta-analysis, the prevalence of H. pylori infection in children with duodenal ulcer was reported as 92% (range: 30-100) (16). In our study, more than half of the children were infected with H. pylori in both the gastric ulcer and duodenal ulcer group.…”
Section: Discussionsupporting
confidence: 63%
“…This scenario is similar in children i.e. when H. pylori-associated ulcers occur in children, duodenal ulceration is much more frequently identified than gastric ulcers [104]. In fact, pooled analysis of early reports (from 1983 to 1994) has demonstrated that the prevalence of H. pylori in children with duodenal ulcer was relatively higher (ranging from 33% to 100%, with a median value of 92%), compared with children with gastric ulcer (ranging from 11% to 75%, with a median value of 25%) [104].…”
Section: Nevertheless Specific Populations Such As Immigrants and Rumentioning
confidence: 90%
“…when H. pylori-associated ulcers occur in children, duodenal ulceration is much more frequently identified than gastric ulcers [104]. In fact, pooled analysis of early reports (from 1983 to 1994) has demonstrated that the prevalence of H. pylori in children with duodenal ulcer was relatively higher (ranging from 33% to 100%, with a median value of 92%), compared with children with gastric ulcer (ranging from 11% to 75%, with a median value of 25%) [104]. A more recent retrospective study (from 1995 to 2001) from Japan confirmed a very high prevalence of H. pylori in antral gastritis and duodenal ulcer (98.5% and 83%, respectively), also identifying H. pylori as a risk factor for the development of gastric ulcer although with a lower prevalence of infection (less than 50%) [101].…”
Section: Nevertheless Specific Populations Such As Immigrants and Rumentioning
confidence: 99%
“…11 In subsequent studies using his criteria the prevalence ranged from 11% to 45%. [11][12][13][14] The width of this range is probably attributable to differences in age, geographical area and social factors and methodology. Nevertheless, recurrent abdominal pain is clearly no less troublesome now than when Apley described it in 1958.…”
Section: Methodsmentioning
confidence: 99%